Particular model for improving failure mode and effect analysis (FMEA) by using of overall equipment efficiency (OEE) - Esmaeilian, Gholamreza; Megat Ahmad, Megat Mohamad Hamdan; Ismail, Napsiah; Sulaiman, Shamsuddin; Hamedi, Maryam (IEEE, 2008)
Almost all of factories use failure mode and effect analysis (FMEA) technique to reduced risk priority number (RPN). This paper proposes a new model to reduce RPN by improving overall equipment efficiency (OEE) by using of heuristic mathematic model based on total productive maintenance index. Three factors are considered: (i) probability of failure (Occurrence), (ii) severity and (iii) distinction. A textile industry is used as a test case that produces some product for seat cover. It was shown that the RPN decreased in FMEA.